Petrologia magnética dos granitóides Arqueanos de Água Azul do Norte - Província Carajás - SANTOS, Lucy Soares dos (2020)
Água Azul do Norte region is located in the northern of the Carajás Province, comprising the southern portions of the Carajás Domain and North of Rio Maria Domain, where occur Mesoarchean granitic rocks of different natures. They are: i) Tonalitic-Trondjemitic-Granodioritic associations (TTG); ii) high-Mg, represented by Água Azul and Água Limpa sanukitoides; iii) high Ba-Sr, formed by Nova Canadá Leucogranodiorite; iv) high-K, represented by rocks of the Boa Sorte Granite, Velha Canadá leucogranite and porphyritic undifferentiated granites; and v) Grotão Granodiorite which differs from high-K leucogranite for being the poorest in incompatible elements. The magnetic susceptibility values obtained for these range from granitic 2,70x10-6 and 2,78x10-2 SIv, and which can be divided into three magnetic populations. The Grotão Granodiorite and high-Mg granitic concentrated in the less magnetic population (B and C), whereas the high-K units, high Ba-Sr and TTG association have a broad distribution with more significant concentration on the magnetic populations (A and B). Magnetite is Fe-Ti main mineral in the most magnetic populations, whereas in the intermediaries SM values population besides the magnetite there is an association with ilmenite and hematite, which is usually absent in rocks with lower SM values. The high-Ba-Sr, high-K leucogranite and TTG are connected to composite parageneses by titanite (idiomorphic) + magnetite + quartz association indicate relatively high fO2 conditions similar to the HITMQ buffer. Processes that occurr in subsolidus conditions (martitization) indicate an increase fO2, showing that HM buffer above conditions were reached at this stage. The Sanukitoides and Grotão Granodiorite have identical magnetic behavior. The first, feature mineralogical associations like Sanukitoid Suit of Rio Maria Domain, and it is assumed that these rocks were formed between the buffers HM and FMQ. Low concentrations of opaque minerals and rocks such magnetite, resulting in their lower SM values are related to the significant modal content magmatic epidote, formed from the replacement of magnetite. Other high-Mg rocks are related to the formation of magnetite in part replacing the magmatic epidote, during the deformation event and recrystallization.